2014
DOI: 10.1007/s13197-014-1533-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and mode of action of selected glucosinolate hydrolysis products against bacterial pathogens

Abstract: Plants contain numerous components that are important sources of new bioactive molecules with antimicrobial properties. Isothiocyanates (ITCs) are plant secondary metabolites found in cruciferous vegetables that are arising as promising antimicrobial agents in food industry. The aim of this study was to assess the antibacterial activity of two isothiocyanates (ITCs), allylisothiocyanate (AITC) and 2-phenylethylisothiocyanate (PEITC) against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 93 publications
(123 reference statements)
2
83
0
4
Order By: Relevance
“…Moreover, the interaction between isothiocyanate groups and thiol or amine groups of microbial proteins may induce oxidative stress responses and alter cellular redox homeostasis (Dufour et al 2015). In this sense, aromatic glucosinolate-derived isothiocyanates had higher levels of reactivity due to their ability to act as electron donors from the benzene ring (Borges et al 2015). Borges et al (2015) also found that isothiocyanates can act on bacterial cell membranes because these compounds are able to interact with external membrane proteins and penetrate into the cytoplasm, decreasing bacterial growth and leading to their death.…”
Section: Defense Against Biotic Stressmentioning
confidence: 99%
“…Moreover, the interaction between isothiocyanate groups and thiol or amine groups of microbial proteins may induce oxidative stress responses and alter cellular redox homeostasis (Dufour et al 2015). In this sense, aromatic glucosinolate-derived isothiocyanates had higher levels of reactivity due to their ability to act as electron donors from the benzene ring (Borges et al 2015). Borges et al (2015) also found that isothiocyanates can act on bacterial cell membranes because these compounds are able to interact with external membrane proteins and penetrate into the cytoplasm, decreasing bacterial growth and leading to their death.…”
Section: Defense Against Biotic Stressmentioning
confidence: 99%
“…Of interest is the effect that ITC‐producing bacteria have on other microorganisms of the human gut. ITCs are known to have antibacterial properties and it is possible that there may be an overall negative effect on other functions of the gut microbiota. This however, would be dependent on the concentrations of ITCs in the human gut and as yet this question has not been fully addressed .…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, the activated glucosinolates appear applicable to the treatment of human infections and may be used in combination therapy with existing antibiotics. Comparison of the antibiotic activities of SFN and AITCs with that of Vancomycin showed that all contained significant bactericidal activity [4,7,11,65,78]. Sulphoraphane was at least as effective an antibiotic as Vancomycin and was more potent in all bacteria tested.…”
Section: Growth Of Plantsmentioning
confidence: 97%
“…The myrosinase-glucosinolate system evolved in plants of the Capparales order as a protective mechanism aimed against, bacterial and fungal infection and attack by parasites or insects [4,7,11,65,78]. Significantly, the activated glucosinolates appear applicable to the treatment of human infections and may be used in combination therapy with existing antibiotics.…”
Section: Growth Of Plantsmentioning
confidence: 99%
See 1 more Smart Citation